Hopf Algebras and Associative Representations of Two-Dimensional Evolution . - Cabrera-Casado, Yolanda; Cardoso Gonçalves, Maria Inez; Gonçalves, Daniel; Martín-Barquero, Dolores; Martín-González, Cándido; Ruiz Campos, Iván (Springer Nature, 2024)
In this paper, we establish a connection between evolution algebras of dimension two and Hopf algebras, via the algebraic group of automorphisms of an evolution algebra. Initially, we describe the Hopf algebra associated with the automorphism group of a 2-dimensional evolution algebra. Subsequently, for a 2-dimensional evolution algebra A over a field K, we detail the relation between the algebra associated with the (tight) universal associative and commutative representation of A, referred to as the (tight) p-algebra, and the corresponding Hopf algebra, H , representing the affine group scheme Aut(A). Our analysis involves the computation of the (tight) p−algebra associated with any 2-dimensional evolution algebra, whenever it exists. We find that Aut(A) = 1 if and only if there is no faithful associative and commutative representation for A. Moreover, there is a faithful associative and commutative representation for A if and only if H ̸∼= K and char(K) ̸= 2, or H ̸∼= K(ϵ) (the dual numbers algebra) and H ̸∼= K in case of char(K) = 2. Furthermore, if A is perfect and has a faithful tight p-algebra, then this p-algebra is isomorphic to H (as algebras). Finally, we derive implications for arbitrary finite-dimensional evolution algebras
https://openpolicyfinder.jisc.ac.uk/id/publication/7875
Keywords: Hopf, Algebras de; Topología algebraica; Variedades algebraicas; Automorfismos; Evolution algebra; Hopf algebra; Affine group scheme; Faithful representation; Automorphism